Screening for resistance to Fusarium wilt - Bioversity International (Bioversity International, 2015)
Fusarium wilt of banana, caused by the fungal pathogen Fusarium oxysporum f. sp. cubense (Foc), has widely been considered as one of the most devastating diseases in agricultural history, until resistant Cavendish banana cultivars replaced susceptible ones in Central America. New outbreaks of the disease on hitherto resistant cultivars in Asia and more recently in Africa and Australia, caused by the Tropical race 4 (TR4) strain of the pathogen, have raised concerns that the disease is, once again, threatening banana production in the world.